Financial liberalization and foreign bank entry on bank performance - Haris, Balkis; ., . (International Journal of Engineering and Technology, 2018)
Financial sector liberalization had announced by Central Bank of Malaysia in 2009 with the expectation to increase a resilient, diversified and efficient financial sector. Moreover, financial liberalization is intended to increase competitiveness between local and foreign financial institutions in ensuring that overall financial stability and soundness is preserved. The main objective of this study is to measure the effectiveness of financial liberalization implemented by Central Bank of Malaysia in 2009. In particular, this study would like to investigate whether the financial liberalization and the type of bank, size of the bank, liquidity, leverage and bank status explained the Malaysia banking performance. The sample use in this study are all the listed banks totaling 477 yearly-sample data collected from Bankscope. This study suggests that local bank performance is better in the post-financial liberalization period. This result is similar even after applying the trimming method to reduce the outliersâ€™ bias. The study also suggest that conventional banks performances are better than Islamic banks regardless whether it is local or foreign ownership. Hence, it can be concluded that, the bank performance is better for local banks in the post-financial liberalization period and suggests that the financial liberalization by Central Bank of Malaysia to stabilize the financial market and increase local bank performance has been effective in achieving its aim.Â Â